Study the Effect of Some Soil Properties on their Reflection in Digital Imaging Technology - Taha AlJawwadi; Jasim AlRawi (مجلة جامعة كركوك للعلوم الزراعية)
Soil has many chemical and physical characteristic, which influence on soil's color and reflectance. Despite the multiplicity of studies on the effect of soil color properties with modern techniques development as the digital camera, but these experiments have not been tested yet with these techniques. So in this research many crushed surface soil samples were token, then placed in petri dish and photographed with a white calibration paper, after that reflectance calculated by using special program to convert the digital image to values could be studied and drew curves and figure to simple imagination and understanding. The study refers to that there is a clear contrast between air-dry soil and moist soil when there is a difference in some soil properties like texture, while there is no an obvious different in contrast in variant moist level.